2021
DOI: 10.1111/jog.14665
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MIR22HG is downregulated in adenomyosis and upregulates miR‐2861 through demethylation to inhibit endometrial cell proliferation

Abstract: Aim Endometrial cell proliferation plays a critical role in adenomyosis. It has been reported that MIR22HG and miR‐2861 play similar roles in regulating endometrial cell proliferation, indicating their involvement in adenomyosis. This study aimed to investigate the potential involvement of MIR22HG and miR‐2861 in adenomyosis. Methods Endometrial biopsy was collected from both adenomyosis (n = 45) and the healthy controls (n = 45). The expression of MIR22HG and miR‐2861 in biopsies were determined by quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Both MIR22HG and miRNA-2861 were significantly downregulated in AM patient tissues. Cell proliferation assays revealed that MIR22HG may upregulate miRNA-2861 through demethylation, which in turn downregulates STAT3 and MMP2 and inhibits endometrial cell proliferation, suggesting that MIR22HG and miRNA-2861 overexpression may be potential therapeutic target genes for AM ( Yu et al, 2021 ). Taken together, these data suggest that EXOs can regulate cell proliferation and apoptosis through the proteins and miRNAs they transport, thus participating in the development of AM.…”
Section: Relevance Of Exos In Am Pathogenesismentioning
confidence: 99%
“…Both MIR22HG and miRNA-2861 were significantly downregulated in AM patient tissues. Cell proliferation assays revealed that MIR22HG may upregulate miRNA-2861 through demethylation, which in turn downregulates STAT3 and MMP2 and inhibits endometrial cell proliferation, suggesting that MIR22HG and miRNA-2861 overexpression may be potential therapeutic target genes for AM ( Yu et al, 2021 ). Taken together, these data suggest that EXOs can regulate cell proliferation and apoptosis through the proteins and miRNAs they transport, thus participating in the development of AM.…”
Section: Relevance Of Exos In Am Pathogenesismentioning
confidence: 99%
“…It has been demonstrated that several microRNAs are dysregulated in endometrium from adenomyosis patients, raising hopes of developing a treatment by normalizing expression of these molecules [ 74 ]. According to subsequent studies, let-7a, miR-145-5p, miR-17, and miR-2861 have all been found to be differentially expressed in adenomyosis and may constitute targets for development of novel therapies against the disease [ 75 , 76 , 77 , 78 ]. Nevertheless, there is still a huge gap to bridge between in vitro studies and development of a drug for clinical application, with the first ever small RNA-based therapeutic (patisiran) only obtaining FDA approval as recently as 2018.…”
Section: Medical Treatment Of Adenomyosismentioning
confidence: 99%